La mente rituale. Dalla nascita del rito all’origine delle istituzioni umane - Chiera, Alessandra (Rivista Italiana di Filosofia del Linguaggio, 2014)
In this paper we make reference to the debate about the nature, the evolution and the mechanisms underlying social rituals from a naturalistic point of view. Considering current observations coming from the phylogenetic perspective, we explore two prevailing and opposite accounts of the ritual dimension which characterizes social groups: on the one hand, a non-adaptationist approach argues that ritual is essentially “derivative”, that is, represents a dysfunctional by-product of cognitive adaptations arisen for other purposes; by contrast, the adaptationist model claims that ritualistic actions have a specific value for social cooperation and, hence, are part of an evolutive line tied to socially adaptative behaviors. Consistent with the latter account, we examine the specific hypothesis that the development of complex human rituals has been fostered by the emotional components tied to ritualization involved in collective animal practices. To this extent, we argue that emotionally-charged rituals have played a crucial role in the origin and the evolution of social constraints underlying the articulated human institutions.